The secret language of color : science, nature, history, culture, beauty of red, orange, yellow, green, blue & violet - Eckstut, Joann; Eckstut, Arielle (Black Dog & Leventhal Publishers : Distributed by Workman Pub., 2013)
"Explores color's countless manifestations, providing insight into such phenomena as the visible spectrum, light absorption and reflection, how humans see color, how vision evolved, the sky, rainbows, colored gems, animal pigmentation, how animals use color to find mates and to protect themselves, and the use of color in human religion, ritual, design, navigation, communication, and personal identity."
Keywords: barvy; colors; populárně-naučné publikace; popular works